The controlled release of a novel thiolated icariin for enhanced osteoporotic bone regeneration. (15th February 2021) - Luo, Zhaocong; Chen, Xuening; Liu, Minjun; Wang, Yuyi; Li, Dongxiao; Li, Xiangfeng; Xiao, Yumei; Wang, Yan; Zhang, Xingdong
Abstract: The regeneration of bone defects in osteoporotic patients presents a big challenge. Icariin (Ica), which is the main active component of traditional Chinese medicine - herba epimedii, has been widely loaded to scaffolds for the treatment of bone fracture and osteoporosis. To increase drug loading capacity, and meanwhile achieve a stable and safe drug delivery, in present study, a novel icariin derivative - thiolated icariin (Ica-SH) molecule with good cytocompatibility and bioactivity was incorporated into biphasic calcium phosphate (BCP) ceramic scaffold through Ica-SH intermolecular disulfide bonds ( abbr., Ica-SH/BCP) to form film coating. Compared with Ica-loaded BCP scaffolds via physical adsorption (abbr., Ica/BCP), the formation of Ica-SH intermolecular disulfide bonds in Ica-SH/BCP scaffolds led to a decreased real-time drug release concentration, and a reduced drug release rate. The released drug from Ica-SH/BCP scaffolds could promote the proliferation, migration, and osteoblastic differentiation of ovariectomized rat bone mesenchymal stem cells (OVX-rBMSCs), and up-regulate the angiogenic gene expression in human umbilical vein endothelial cells (HUVECs) in vitro . The OVX-rat femoral condyle defect model also demonstrated that Ica-SH/BCP scaffolds promoted a superior bone regeneration in osteoporotic animals than BCP ones. These findings suggest that Ica-SH is a promising drug, which can be facilely incorporated into a variety of scaffolds for repairing bone defects of patients, in particular the ones with osteoporosis. Graphical abstract: Unlabelled Image Highlights: Thiolated icariin (Ica-SH) was incorporated into BCP scaffold by intermolecular disulfide bonds (Ica-SH/BCP). Ica-SH/BCP scaffold displayed superior loading and releasing performance. Ica-SH/BCP scaffold enhanced migration and osteogenic differentiation of ovariectomized rat bone mesenchymal stem cells. Ica-SH/BCP scaffold promoted osteoporotic bone regeneration of ovariectomized rat.